Innovative Techniques for Rapid MSE Wall Installation - Sah, Nandkishor; Thakur, Abhilash (Journal of Science and Technology, 2025)
This study explores innovative techniques for the rapid installation of Mechanically Stabilized Earth (MSE) walls, focusing on advancements that enhance efficiency and reduce construction time. MSE walls, known for their strength and versatility, are widely used in retaining structures, but traditional installation methods can be time-consuming and labor-intensive. This research investigates novel approaches and technologies aimed at accelerating the installation process while maintaining structural integrity and cost-effectiveness. Techniques such as pre-fabricated panels, automated assembly systems, and advanced material technologies are evaluated for their potential to streamline the construction workflow. The study incorporates case analyses of recent projects employing these innovations, assessing their impact on construction speed, quality, and overall project costs. Additionally, the research highlights the benefits and challenges associated with each technique, offering insights into practical applications and best practices. By identifying and analyzing cutting-edge solutions, this study aims to provide valuable recommendations for the construction industry to optimize MSE wall installation processes, ultimately contributing to more efficient and sustainable infrastructure development.